2022
DOI: 10.1007/s00122-022-04087-y
|View full text |Cite
|
Sign up to set email alerts
|

Genomic selection for spot blotch in bread wheat breeding panels, full-sibs and half-sibs and index-based selection for spot blotch, heading and plant height

Abstract: Key message Genomic selection is a promising tool to select for spot blotch resistance and index-based selection can simultaneously select for spot blotch resistance, heading and plant height. Abstract A major biotic stress challenging bread wheat production in regions characterized by humid and warm weather is spot blotch caused by the fungus Bipolaris sorokiniana. Since genomic selection (GS) is a promising selection tool, we evaluated its potential for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 91 publications
0
10
1
Order By: Relevance
“…The index-based selection was found to be particularly useful for negatively correlated traits that are hard to simultaneously improve [ 82 ], which was the case between grain yield and GPC, yield and plant height, and maturity and GPC in both conventional and organic management systems ( Figure 1 ). In such cases, phenotypic selection indices have been used for simultaneously improving multiple negatively correlated traits in wheat, including grain yield and GPC [ 83 ], spot blotch resistance, early maturity, and short plant height [ 60 ], Helminthosporium leaf blight resistance, early maturity, grain yield, and kernel weight [ 82 ]. In oat, Dolan et al [ 84 ] reported the superiority of both the restricted index and Smith index, as compared with selection for grain yield alone, for simultaneously improving heading date, plant height, and barley yellow dwarf virus resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The index-based selection was found to be particularly useful for negatively correlated traits that are hard to simultaneously improve [ 82 ], which was the case between grain yield and GPC, yield and plant height, and maturity and GPC in both conventional and organic management systems ( Figure 1 ). In such cases, phenotypic selection indices have been used for simultaneously improving multiple negatively correlated traits in wheat, including grain yield and GPC [ 83 ], spot blotch resistance, early maturity, and short plant height [ 60 ], Helminthosporium leaf blight resistance, early maturity, grain yield, and kernel weight [ 82 ]. In oat, Dolan et al [ 84 ] reported the superiority of both the restricted index and Smith index, as compared with selection for grain yield alone, for simultaneously improving heading date, plant height, and barley yellow dwarf virus resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Each index is defined as a linear combination of either the observed mean phenotypic values of the traits of interest with the trait’s economic weights predefined by breeders, or both phenotype and genomic (molecular markers) data [ 50 , 56 ]. Selection indices have been used in several species, including wheat [ 40 , 57 , 58 , 59 , 60 ]. Most breeders, however, do not routinely use selection indices, due to the need for a priori knowledge of fixed effects, variance–covariance matrices, and relative economic weights [ 55 , 61 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on a novel approach, an imputation-enabled SNP array, Illumina Infinium Wheat Barley 40K SNP array version 1.0, has been designed to capture the haplotypic diversity in wheat and barley germplasm [ 24 ]. In addition to the reliable and cost-effective SNP chip arrays, NGS-based genotyping-by-sequencing (GBS) has been used to detect global variation in wheat germplasm for various applications [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Genomic Approachesmentioning
confidence: 99%
“…In GS, a set of individuals are genotyped and phenotyped as a training population for use to develop the prediction model ( Juliana et al, 2018 ). The efficacy of GS has been tested for multiple traits in several crops, including wheat, for yield ( Juliana et al, 2018 ), leaf rust and yellow rust ( Juliana et al, 2017 ), spot blotch ( Juliana et al, 2022b ), and wheat blast ( Juliana et al, 2022a ). GS to improve grain mineral concentrations has been employed in maize ( Mageto et al, 2020 ), rice ( Rakotondramanana et al, 2022 ), and wheat ( Velu et al, 2018 ), with reasonable prediction accuracies.…”
Section: New Breeding Techniques For Biofortificationmentioning
confidence: 99%